2005
DOI: 10.1117/12.592747
|View full text |Cite
|
Sign up to set email alerts
|

Software visualization techniques for real-time imaging applications

Abstract: Real-time imaging applications are concerned with efficient and deterministic processing of digital images. These applications are predominantly written using structured programming rather than object-oriented programming with the belief that the former approach has better performance characteristics. Current research shows that this may not be the case and an object-oriented approach may not only result in efficient code but one that is more maintainable and understandable. We look at current techniques for v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…A study was performed which showed which applying object-oriented design patterns could produce well-designed and efficient image processing systems with easy extensibility, maintainability, and reuse without sacrificing real-time performance. Due to these findings, in [128], it was argued that real-time image processing applications should be written using an object-oriented approach to achieve efficient, maintainable, and understandable code from the start. Such a design approach was shown to be superior since it can eliminate inefficiencies in software that are common in other design approaches.…”
Section: Object-oriented Design Patternsmentioning
confidence: 98%
See 1 more Smart Citation
“…A study was performed which showed which applying object-oriented design patterns could produce well-designed and efficient image processing systems with easy extensibility, maintainability, and reuse without sacrificing real-time performance. Due to these findings, in [128], it was argued that real-time image processing applications should be written using an object-oriented approach to achieve efficient, maintainable, and understandable code from the start. Such a design approach was shown to be superior since it can eliminate inefficiencies in software that are common in other design approaches.…”
Section: Object-oriented Design Patternsmentioning
confidence: 98%
“…One research group has primarily been involved in promoting the use of object-oriented design patterns for such systems as discussed in the references [90,104,127,128].…”
Section: Object-oriented Design Patternsmentioning
confidence: 99%